Moms don't have time to have kids : a timeless anthology - Owens, Zibby (Skyhorse Publishing, 2021)
Essays by authors who have appeared on the podcast "Moms Don't Have Time to Read Books" explore the ever-increasing demands on mothers' time and topics inspired by things moms don't have time to do, including sleep, get sick, write, lose weight, and see friends.